Reporting the Holocaust in the British, Swedish and Finnish press, 1945 - 50 - Holmila, Antero 1979- (The Holocaust and its contexts, 2011)
"Examining how the press in Britain, Sweden and Finland responded to the Holocaust immediately after the Second World War, Holmila offers new insights into the challenge posed by the Holocaust for liberal democracies by looking at the reporting of the liberation of the camps, the Nuremberg trial and the Jewish immigration to Palestine."--